Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T19:37:18+01:00
A) 4x-(x+6)+4 = dla x=1/3
=4x-x-6+4 =
= 3x-2 =
= 3*1/3-2 = 1-2 = -1

b) (x+1)-(x-2)+10 = dla x=2,2
= x+1-x+2+10 =
= 13

c) (a+4b)-(5+2a)-(3b-5)= dla a= -0,1 i b= 0,2
= a+4b-5-2a-3b+5 =
= -a+b =
= 0,1+0,2 = 0,3

d) (-a+2ab-1)-(a-4ab+5) = dla a=1/4 i b=2
= -a+2ab-1-a+4ab-5 =
= -2a+6ab-6 =
= -2*1/4 + 6*1/4*2-6 =
= -1/2+3-6 =
= -0,5+3-6 =
= 2,5-6 = -3,5
2010-02-25T19:44:25+01:00
A) 4x-(x+6)+4 dla x=⅓
4*1/3-(1/3+6)+4=4/3-19/3+4=-15/3+4=-5+4=-1
b) (x²+1)-(x²-2)+10 dla x=2,2
(4,84+1)-(4,84-2)+10=5,84-2,84+10=3+10=13
c) (a+4b) - (5+2a)-(3b-5) dla =-0,1 i b=0,2
(-0,1+4*0,2)-(5+2*-0,1)-(3*0,2-5)=(-0,1+0,8)-(5-0,2)-(0,6-5)=
=0,7-4,8-(-4,4)=-4,1+4,4=0,3
d) (-a²+2ab-1)+(a²-4ab+5) dla a=¼ i b=2
(-1/16+1-1)+(1/16-2+5)=-1/16+1/16+3=3
2010-02-25T19:47:51+01:00
A) 4x-(x+6)+4 dla x=⅓
4*1/3-(1/3+6)+4=4/3-19/3+4=-15/3+4=5+4=9
b) (x²+1)-(x²-2)+10 dla x=2,2
(4,84+1)-(4,84-2)+10=5,84-2,84+10=3+10=13
c) (a+4b) - (5+2a)-(3b-5) dla =-0,1 i b=0,2
(-0,1+4*0,2)-(5+2*-0,1)-(3*0,2-5)=(-0,1+0,8)-(5-0,2)-(0,6-5)=
=0,7-4,8-(-4,4)=-4,1+4,4=0,3
d) (-a²+2ab-1)+(a²-4ab+5) dla a=¼ i b=2
(-1/16+1-1)+(1/16-2+5)=-1/16+1/16+3=3